Tribolium castaneum as an experimental model for studies of lipid and carbohydrates metabolism: a technological prospection - Silva, Meirielly Kellya Holanda (2020)
A technological survey was carried out aiming at analyzing patent filing requests regarding the use of Tribolium castaneum as an experimental model for studies in carbohydrate and lipid metabolism, through patents from the PatentScope and Espacenet databases, and scientific articles from PubMed. Most deposit orders refer to pest repellants/pest control, which is explained by the fact that Tribolium castaneum is one of the main stored grain pests with worldwide distribution. Thus, none of the analyzed applications refers to its use as an experimental model for studies in carbohydrate and lipid metabolism, as well as no scientific article was found explaining its development. In view of this gap, it is concluded that this is a technological area little explored and potentially useful for new research and products.